A Prototype N95 Sterilizer: An Alternative Solution during Personal Protective Equipment Crisis - Azhar, Muh. Aprizal; Natzir, Rosdiana; Sjahril, Rizalinda; Palantei, Elyas; Katu, Sudirman; Hidayah, Najdah; Massi, Muhammad Nasrum (Indonesian Journal of Tropical and Infectious Disease, 2022)
The high demand for N95 masks, especially during the COVID (Coronavirus disease)-19 pandemic, has caused shortages worldwide. This study aimed to examine the sterilization ability of the portable sterilizer prototype for N95 masks and its effect on the filtration ability and changes in air resistance on the N95 mask in order to thrift personal protective equipment (PPE) use during a shortage. The sample used was an N95 mask type 1860. The mask was contaminated with 0.6-0.8 MFU Staphylococcus aureus and Escherichia coli. The sterilization methods used were Ultraviolet Germicidal Irradiation (UVGI), Heat at 75°C, and a combination of both from 1 to 120 minutes. Next, the masks were cultured in a nutrient agar medium. For aerosol penetration and air resistance tests, masks were tested before and after the sterilization process, lasting from 5 to 60 minutes. This prototype sterilizer with Heat effectively killed E. coli and S. aureus starting from 3 minutes. The filtration ability of the N95 mask was maintained at >95% even after the sterilization process with 75°C heat, UVC, or a combination of both for up to 60 minutes. There was also no significant difference in air resistance between new masks and masks that had been sterilized using a portable sterilizer. This prototype sterilizer with Heat at 75°C can effectively sterilize against both gram-positive and negative bacteria in the N95 mask without reducing the aerosol filtration ability and changing the air resistance of the N95 mask.